Mammalian enamel maturation: Crystallographic changes prior to tooth eruption. - Anna Kallistová; Ivan Horáček; Miroslav Šlouf; Roman Skála; Michaela Fridrichová (PLoS ONE, 2017)
Using the distal molar of a minipig as a model, we studied changes in the microstructural characteristics of apatite crystallites during enamel maturation (16-23 months of postnatal age), and their effects upon the mechanical properties of the enamel coat. The slow rate of tooth development in a pig model enabled us to reveal essential heterochronies in particular components of the maturation process. The maturation changes began along the enamel-dentine junction (EDJ) of the trigonid, spreading subsequently to the outer layers of the enamel coat to appear at the surface zone with a 2-month delay. Correspondingly, at the distal part of the tooth the timing of maturation processes is delayed by 3-5 month compared to the mesial part of the tooth. The early stage of enamel maturation (16-20 months), when the enamel coat is composed almost exclusively of radial prismatic enamel, is characterized by a gradual increase in crystallite thickness (by a mean monthly increment of 3.8 nm); and an increase in the prism width and thickness of crystals composed of elementary crystallites. The late stage of maturation (the last two months prior to tooth eruption), marked with the rapid appearance of the interprismatic matrix (IPM) during which the crystals densely infill spaces between prisms, is characterized by an abrupt decrease in microstrain and abrupt changes in the micromechanical properties of the enamel: a rapid increase in its ability to resist long-term load and its considerable hardening. The results suggest that in terms of crystallization dynamics the processes characterizing the early and late stage of mammalian enamel maturation represent distinct entities. In regards to common features with enamel formation in the tribosphenic molar we argue that the separation of these processes could be a common apomorphy of mammalian amelogenetic dynamics in general.